Pengaruh Lama Senam Hamil Terhadap Tingkat Rasio Kecemasan Menghadapi Proses Persalinan Normal Di Puskesmas Pondok Labu Tahun 2023 - Sumarni; Kaman, Safria Indah (Lembaga Publikasi Ilmiah Nusantara, 2024)
The process of childbirth can lead to various psychological aspects that may cause a range of psychological problems, one of which is anxiety. Anxiety is one of the most common feelings experienced by pregnant women as they approach labor. According to the World Health Organization (2020), approximately 10% of pregnant women and 15% of women who have recently given birth experience mental health problems, particularly depression. The prevalence rates are even higher in developing countries, reaching 15.6% during pregnancy and 19.8% postpartum. In Indonesia, the incidence of anxiety among pregnant women is reported to be around 373,000 cases. Of these, 107,000 cases, or 28.7%, involve moderate anxiety occurring as women approach labor. The aim of this study was to examine the effect of prenatal exercise on anxiety levels in facing the childbirth process. The research design was a quasi-experimental study using a pretest-posttest control group design. In this study, the experimental group received an intervention in the form of prenatal exercise, while the control group did not undergo any prenatal exercise. The sample consisted of 40 respondents. The study was conducted at Pondok Labu Community Health Center, South Jakarta. Data were analyzed using univariate and bivariate methods, with a T-Test for statistical analysis. The results showed that prenatal exercise had a significant effect on reducing anxiety levels before childbirth (p-value = 0.000). It is recommended that pregnant women familiarize themselves with prenatal exercise procedures as a strategy to manage anxiety before labor.